Ըղձական եղանակի իմաստագործաոական առանձնահատկություններն անկախ նախադասություններում իտալերենում, հայերենում և անգլերենում - Իռեն Սանթրոպան (ՀՀ ԳԱԱ հրատ.)
The article touches upon the semantic-functional characteristics of the subjunctive mood in independent clauses in Italian, Armenian and English. Here we speak about the notable difference between the morphological mood and the syntactic one, emphasizing that the morphological mood is defined as a form distinguished, both for the morphological and syntactic characteristics, from the other verbal moods, while to define the concept of the syntactic mood we should take as starting point the morphological mood and its functions within the limits of the modal schemes.
Keywords: Language and Literature